Cost-effectiveness and Budgetary Impact of Hepatitis C Virus Testing, Treatment, and Linkage to Care in US Prisons. (16th May 2019) - Assoumou, Sabrina A; Tasillo, Abriana; Vellozzi, Claudia; Eftekhari Yazdi, Golnaz; Wang, Jianing; Nolen, Shayla; Hagan, Liesl; Thompson, William; Randall, Liisa M; Strick, Lara; Salomon, Joshua A; Linas, Benjamin P
Abstract: Background: Hepatitis C virus (HCV) testing and treatment uptake in prisons remains low. We aimed to estimate clinical outcomes, cost-effectiveness (CE), and budgetary impact (BI) of HCV testing and treatment in United States (US) prisons or linkage to care at release. Methods: We used individual-based simulation modeling with healthcare and Department of Corrections (DOC) perspectives for CE and BI analyses, respectively. We simulated a US prison cohort at entry using published data and Washington State DOC individual-level data. We considered permutations of testing (risk factor based, routine at entry or at release, no testing), treatment (if liver fibrosis stage ≥F3, for all HCV infected or no treatment), and linkage to care (at release or no linkage). Outcomes included quality-adjusted life-years (QALY); cases identified, treated, and cured; cirrhosis cases avoided; incremental cost-effectiveness ratios; DOC costs (2016 US dollars); and BI (healthcare cost/prison entrant) to generalize to other states. Results: Compared to "no testing, no treatment, and no linkage to care, " the "test all, treat all, and linkage to care at release" model increased the lifetime sustained virologic response by 23%, reduced cirrhosis cases by 54% at a DOC annual additional cost of $1440 per prison entrant, and would be cost-effective. At current drug prices, targeted testing and liver fibrosis–based treatment provided worse outcomes at higher cost or worse outcomes at higher cost per QALY gained. In sensitivity analysis, fibrosis-based treatment restrictions were cost-effective at previous higher drug costs. Conclusions: Although costly, widespread testing and treatment in prisons is considered to be of good value at current drug prices. Abstract : We used simulation modeling to show that hepatitis C virus (HCV) testing and treatment in prison or linkage to care for individuals not treated in prison was cost-effective, but costly. Addressing HCV in prisons will require partnerships.